Mimivirus is not a frequent cause of ventilator‐associated pneumonia in critically ill patients. Issue 10 (16th July 2013) - Vanspauwen, M.J.; Schnabel, R.M.; Bruggeman, C.A.; Drent, M.; van Mook, W.N.K.A; Bergmans, D.C.J.J.; Linssen, C.F.M.
Abstract Acanthamoeba polyphaga mimivirus (APMV) belongs to the amoebae‐associated microorganisms. Antibodies to APMV have been found in patients with pneumonia suggesting a potential role as a respiratory pathogen. In addition, positive serology for APMV was associated with an increased duration of mechanical ventilation and intensive care unit stay in patients with ventilator‐associated pneumonia. The aim of the present study was to assess the presence of APMV in bronchoalveolar lavage fluid samples of critically ill patients suspected of ventilator‐associated pneumonia. The study was conducted in the intensive care unit of the Maastricht University Medical Centre. All consecutive bronchoalveolar lavage fluid samples obtained between January 2005 and October 2009 from patients suspected of ventilator‐associated pneumonia were eligible for inclusion. All samples were analyzed by real‐time PCR targeting the APMV. A total of 260 bronchoalveolar lavage fluid samples from 214 patients (139 male, 75 female) were included. Bacterial ventilator‐associated pneumonia was confirmed microbiologically in 105 out of 260 (40%) suspected episodes of ventilator‐associated pneumonia (86 patients). The presence of APMV DNA could not be demonstrated in the bacterial ventilator‐associated pneumonia positive or in the bacterial ventilator‐associated pneumonia negative bronchoalveolar lavage fluid samples. Although suspected, APMV appeared not to be present in critically ill patients suspected of ventilator‐associated pneumonia, and APMV does not seem to be a frequent cause of ventilator‐associated pneumonia. J Med. Virol. 85:1836–1841, 2013. © 2013 Wiley Periodicals, Inc.